ESG Practices, Access to Finance, and Firm Performance among Malaysian SMEs: A Trust-Based Capability Perspective - Nur Aina Hamzah Nur Aina Hamzah; Siti Farhana Ismail Siti Farhana Ismail; Ahmad Faizal Rahim Ahmad Faizal Rahim (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2025)
This study examines how ESG practices relate to SME performance in Malaysia, focusing on the enabling role of access to finance and the moderating influence of market turbulence. Drawing on the Resource-Based View and stakeholder-oriented trust mechanisms, we conceptualize ESG as an organizational capability that can strengthen legitimacy and reduce perceived risk, thereby improving financing outcomes and operational performance. Survey data were collected from 402 Malaysian SMEs across manufacturing, services, and agribusiness sectors. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the analysis indicates that ESG practices are positively associated with firm performance, with access to finance operating as a partial mediator. The relationship strengthens under higher market turbulence, suggesting that ESG operates as a resilience-enhancing capability when external volatility increases. The study contributes to ESG literature by explaining performance pathways in the SME context and offering an ASEAN-relevant perspective on how sustainability-related capabilities translate into tangible outcomes. The findings suggest that policy initiatives supporting ESG adoption—especially those linked to green financing and disclosure assistance—may improve both firm competitiveness and financial inclusion among SMEs.